Discovery Learning Based Practicum Learning in Improving Critical Thinking Skill and Student Creativity - Firdiawan Ekaputra; Sri Widarwati (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
Memorization activities in learning make students' critical thinking skills and creativity unable to develop. This study aimed to determine the effectiveness of the discovery learning model in practicum activities in improving students' critical thinking skills and creativity. The research design is a quasi-experimental model. The sample used in this study were students of the Chemistry Education Study Program at Jambi University who took the inorganic chemistry practicum course in the 2022/2023 academic year, class R-002, the experimental class, and class R-004, the control class. The questionnaire instrument obtained data on critical thinking skills and creativity. Data analysis techniques to determine the increase in critical thinking skills and creativity after applying the discovery learning model using the Manova test. The results of this study indicate that practicum learning with the discovery learning model effectively increases students' critical thinking and creativity, especially for Chemistry Education students at Jambi University who are conducting Inorganic Chemistry practicum in the 2022/2023 academic year.